LESSONS LEARNED FOR AGESTAGE REPLICATION AND IMPROVEMENT. (11th November 2018) - Liebig, P S; Chevalier, L
Abstract: An innovative program, such as the AgeStage, can–through lessons learned–inspire adoption or adaptations. Key factors for success include: defining its vision; gaining aging organizations' approvals; qualities of exceptional leadership; convening an expert humanities and arts WorkGroup; and GSA auspices and support. Members were fully committed to securing funding, recruiting and selecting performers, curating through phone calls/webinars, moderating, and problem solving. The stage manager was also key to success, matching audiovisual and venue needs. Through process and outcome evaluation, nine categories of lessons learned are presented, including budgets, marketing and production roles. High levels of diversity were attained among multicultural presenters and in the topics addressed, such as the impact of HIV/AIDS on older adults. Presenters will consider potential improvements and also analyze how the AgeStage achieved such a resounding impact on its audience.